HIV Status Disclosure and Associated Factors among Partners and People Living with HIV in the North Central Region of Nigeria: Factors affecting HIV status disclosure - Olajide, Joshua Seun; Ojo, Adeoye Matthew; Olafisoye, Desmond; Oluwasina , Folajinmi; Ojo, Christiana (Disease Prevention and Public Health Journal, 2024)
Background: Prevention, treatment, and care for people with HIV/AIDS are important foci of public health and control of the disease. HIV has significantly impacted people's health, income and welfare, as well as socialization. Disclosure of HIV status has proven to increase the opportunities for social support, improved access to necessary medical care, and the opportunity to discuss HIV risk reduction with partner's plan. This study examined factors influencing partner HIV status disclosure among people living with HIV in North Central, Nigeria. Method: This descriptive and cross-sectional study used a multistage sampling technique to randomly select 215 respondents receiving antiretroviral treatment in the study location. Results: The results showed that all youngsters aged 15-19 had never disclosed their HIV status to sexual partners due to the fear of discrimination, rejection, and abandonment. The study found a significant association between minimizing the stress of keeping HIV secret and HIV partner disclosure (β=0.944, Odd Ratio OR=2.570, CI=1.79-3.69, p<0.05). Conclusion: The study showed that discrimination and stigmatization are major sources of discouragement in the disclosure of HIV status to partners as well as the fear of rejection and abandonment especially among young adolescents. It is therefore recommended that HIV treatment and awareness programs should incorporate HIV status disclosure and counselling as part of intervention projects for HIV/AIDS programs. HIV status disclosure to partners will foster and promote partner’s understanding, patient's health and well-being. This will not only bring social and psychological support, but also reduce misguidance on HIV status.